Sistem Informasi Penjualan Berbasis Web Pada Alun-Alun Coffee Jakarta - Yunika Lestari; Harfebi Fryonanda (UNIVERSITAS KALBIS, 2022)
Alun Coffee Jakarta is one of the Coffee Shops in East Jakarta. Alun-Alun Coffee sells several variants of Nusantara coffee brewing. In addition, Alun-Alun Coffee also sells several Non-Coffee menus as well as heavy meals, snacks, and desserts. For a few years this added coffee shop business significantly increased growth so that Alun-Alun Coffee increased the number of customers. But now the business activities carried out are less than optimal and focus on the sales process and not involved in it. Requiring companies need an information system as a tool for recording data, processing data, and doing data integration. The development method used for system installation uses prototype. The results of this study are web-based Coffee Sales Information System that online ordering and records, processes, integrates data and becomes a structured data repository so as to increase effectiveness and improve performance and time. Based on the results of research and evaluation of research, the system that has been built provides complete information about online orders by customers and sales transactions at Alun-Alun Coffee.